EFFECT OF EDUCATIONAL INTERVENTION ON THE KNOWLEDGE LEVEL OF GLASGOW COMA SCALE AMONG NURSES AT TERTIARY CARE HOSPITAL KHYBER PAKHTUNKHWA, PAKISTAN (The Research of Medical Science Review, 2024)
Background: The Glasgow Coma Scale (GCS) is a key tool for assessing consciousness in patients with neurological disorders. Given nurses' critical role in caring for these patients, it's essential to assess and improve their knowledge of the GCS through targeted educational programs. Objective: This study aims to assess the impact of an educational intervention on the knowledge and application of the Glasgow Coma Scale among nurses working in a tertiary care hospital. Methods: This quasi-experimental study was conducted at a tertiary care facility in Buner, Pakistan, with a sample of 150 nurses selected through stratified sampling. Data were collected before and after an educational intervention using structured questionnaires. Statistical analysis was performed with SPSS, using paired and independent t-tests, with significance set at p < 0.05 to compare the intervention and control groups. Results: The participant demographics revealed that 83.3% were male and 16.7% were female. The majority, 42.7%, worked in the Intensive Care Unit, followed by 24.7% in the Emergency Department. Initially, knowledge scores were low, but post-intervention results indicated significant improvements, with knowledge scores increasing from a mean of 4.39 to 7.19 with (p = 0.000). Conclusion: The results suggest that the educational intervention successfully enhanced nurses' understanding of the Glasgow Coma Scale; however, notable deficiencies in practical application persist. Over 60% of nurses reported challenges in areas such as identifying motor responses, preparing for assessments, and documenting findings. These outcomes underscore the necessity for ongoing, targeted training initiatives to further develop nurses' proficiency with the GCS and foster reflective practice.